Aspectos bioéticos relacionados aos cuidados paliativos: da abordagem principialista aos direitos humanos - Alves, Isabella Drummond Oliveira Laterza (2023)
This study starts from a theoretical (exploratory-descriptive) and qualitative perspectives, carrying out through a bibliographical survey in the PubMed and Tripdatabase databases, taking as objective to theoretically and critically analyze texts related to palliative care published in the international literature on the perspective bioethics. The data were treated through content analysis with 29 articles included. From the study findings perspective, the following topics were discussed: ability to choose and autonomy; palliative sedation: euthanasia or end-of-life care; suffering and lack of training of health professionals; ethical dilemmas in pandemics; justice and equity and access to health services. It was observed that many bioethical contributions concern the reflections of dignity and autonomy of the seriously ill patient in a situation of terminality of life, the interface between technology and humanized care, and the ethical dilemmas involved such as interruption of life support treatment. Bioethical studies on palliative care promoted better targeting for situations that generate doubts and concerns. It was observed that studies are still centered on principlism, and it is usually up to the health professional (mostly often the doctor) to handle complex situations such as decisions at the end of life. Physicians and health professionals, on the other hand, point out that they were not prepared during graduation and find it difficult to approach the subject. Professionals must be trained to provide assistance based on the philosophy of this type of care and on the principles of Bioethics. Palliative care has evolved over the past five decades as a specialty to improve quality of life and the quality of care for patients and their families. Despite the evolution, there is a lot of confusion, both in relation to patients and family members, about this type of care, where they associate it, for example, with euthanasia.